Hydrogen-assisted suspension roasting for pre-reducing lateritic nickel ore: Comparison with CO reduction - Zhe Bai; Jiahao He; Mingxing Wang; Shaokai Cheng; Shuai Yuan; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Using tea plant synomone (E, E)-α-farnesene to attract parastoid Amitus hesperidum to control Aleurocanthus spiniferus in tea plantations - Yue'er Liang; Yanjun Cheng; Manxia Wu; Shanjie Han; Baoyu Han (Crop Protection, 2026)

A hybrid FVM-FEM simulator for coupled multiphysics: Application to field-scale CO2-ECBM - Yulong Liu; Yanjun Zhang; Guanhong Feng; Yuxiang Cheng; Xuefeng Gao; Tianfu Xu (Computers and Geotechnics, 2026)

High-precision extraction and dynamics of thermokarst lakes in the Three Rivers Source Region using the SVM coupled edge-OTSU based on Sentinel-1 data - Wangping Li; Rongqi Wan; Xiaodong Wu; Xiaoqiang Cheng; Yadong Liu; Yanjun Bian; Heng Du; Niu Wang; Wenbo Wei; Zhaoye Zhou; Xiuxia Zhang; Defu Zou (CATENA, 2026)

Model-based inference of monsoonal moisture from stalagmite and tree-ring δ18O - Qiang Li; Yifan Wu; Jiachuan Wang; Yu Liu; Yanjun Cai; Haiwei Zhang; Liangcheng Tan; Jingyao Zhao; Changfeng Sun; Huiming Song; Yang Xu; Yueer Li; et al. (Quaternary Science Reviews, 2026)

Optimal layout of LID facilities at an urban basin scale in piedmont cities: Case study of Jinan City, China - Yanjun Zhao; Jun Xia; Zongxue Xu; Lei Cheng; Gang Zhao; Xiang Zhang (Journal of Hydrology, 2026)

Contrasting cold season temperature trends between eastern and western mid-latitude Eurasia over the past millennium - Yuan Yao; Yongsong Huang; Lu Wang; Yurui Zhang; Nan Dai; Liang Ning; Hanying Li; Jie Liang; Xiangzhong Li; Yanjun Cai; Hai Cheng (Quaternary Science Reviews, 2026)

High internal phase Pickering emulsions stabilized by submicron composite particles via ultrasound-assisted binding of lysine to whey protein isolate: Interfacial behavior, microstructural evolution and stabilization enhancement - Yanjun Li; Yingying Sui; Luodi Xu; Olayemi Eyituoyo Dudu; Xuenan Gao; Yan Li; Jinju Cheng; Xiaodong Li (Food Chemistry, 2026)

Geochemical and hydrological controls on aragonite versus calcite precipitation in speleothems and paleoclimatic implications - Rui Zhang; Haiwei Zhang; Christoph Spötl; Carlos Pérez-Mejías; Zixin Guan; Heather Stoll; Yanjun Cai; Liangcheng Tan; Fudong Wang; Xunlin Yang; Yan Yang; Lijuan Sha; et al. (Chemical Geology, 2026)

CircGABRB2_006 Drives Malignant Progression and EMT in Papillary Thyroid Carcinoma via the miR-296-5p/FGFR1 Axis - Chuan Wan; Yanjun Guo; Han Guo; Jingjing Zhu; Fangchao Liu; Yunyuan Zhang; Bingfei Cheng; Juanjuan Li; Ying Xin; Bingzi Dong; Weiwei Fu; Dongmei Meng; et al. (Biochemical Genetics, 2026)

Enhancing nattokinase stability through synergistic interactions:Construction and mechanism analysis of multi-level encapsulation structures in fig-like gel beads - Yao Cheng; Yanjun Tong; Shanjun Tao; Shiqi Zhang; Han Jiang; Ruijin Yang (Food Research International, 2026)

High internal phase emulsions stabilized by milk protein-arabinoxylan-quercetin ternary complex: Enhanced environmental stability and fat digestive property (Milk protein-AX-Q complex-stabilized HIPEs: Stability and digestion) - Xuenan Gao; Peizhu Liu; Sirong Li; Olayemi Eyituoyo Dudu; Yanjun Li; Yan Li; Hongfang Yang; Jinju Cheng; Tingsheng Yan (Journal of Food Engineering, 2026)

Improving functional and interfacial performance of whey protein by pH shift combined with enzymatic glycosylation modification and its effect on high internal phase emulsions - Luodi Xu; Peizhu Liu; Yanjun Li; Olayemi Eyituoyo Dudu; Yiping Luo; Jinju Cheng; Yujun Jiang (Innovative Food Science & Emerging Technologies, 2026)

Failure mechanism and damage assessment of talus slopes with varied gradation under seismic loading - Xing Wei; Shitao Cheng; Rui Chen; Xinle Zhai; Jun Feng; Zijian Wang; Yanjun Li; Le Cheng (Landslides, 2026)

Biochar reshapes phosphorus distribution in soil aggregates and improves rice phosphorus uptake - Jiajun Wu; Bin Zhou; Zhehao Huang; Zichuan Li; Jingyuan Pan; Kaihao Zhang; Cheng Liu; Yanjun Chai; Yan Li; Muhammad Azeem; Nicholas Clarke; Shengdao Shan (Soil Ecology Letters, 2026)

Prediction Method and Application of Dynamic Surface Subsidence in Deep-Buried Thick Alluvium Considering Aquifer Consolidation - Shenyi Zhang; Shanxi Wu; Han Zhang; Weijie Wei; Boyuan Cheng; Yanjun Song; Xiujuan Li; Yaochen Wang (Rock Mechanics and Rock Engineering, 2026)

Evolution of non-colinear fault systems from extension to transtension: Northern Dongying Sag, Bohai Bay Basin, East China - Meng Zhang; Kuihua Zhang; Shuang Song; Yanjun Cheng; Zhiping Wu (Journal of Asian Earth Sciences, 2026)

Holocene climate optimum moisture variability in the monsoon marginal zone of northern China revealed by multi-proxy stalagmite records - Shouyi Huang; Yanjun Cai; Gang Xue; Xinhui Zhang; Mei He; Ruoxin Li; Yingying Wei; Le Ma; Xing Cheng; Haiwei Zhang; Hai Cheng (Global and Planetary Change, 2026)

New insights into source of long chain n-alkanes in cave stalagmites - Yinan Zhao; Yuan Yao; Lu Wang; Yunning Cao; Haiwei Zhang; Tingyong Li; Yanjun Cai; Hai Cheng (Geochimica et Cosmochimica Acta, 2026)

CSSL-based GWAS identifies SNPs and candidate genes associated with Verticillium wilt resistance in cotton - Youzhong Li; Xiaohui Jiang; Hongyu Cao; Xinyu Zhang; Zhongxu Lin; Qian-Hao Zhu; Yanjun Li; Fei Xue; Shuaishuai Cheng; Feng Liu; Jie Sun (Theoretical and Applied Genetics, 2026)

Upland Methane Sinks Under Climate Change: Global Patterns, Drivers and Trends - Li Cheng; Wensheng Xiao; Josep Peñuelas; Fei Li; Yanjun Liu; Philippe Ciais; Xiaoqi Zhou (Global Change Biology, 2026)
Well‐aerated upland soils serve as a crucial biological sink for atmospheric methane (CH 4 ), playing a key role in mitigating climate change. However, current understanding of how this CH 4 sink responds to global climate change remains limited. To address this, we integrated 1092 observational data points to construct a dataset covering multiple global change factors and used meta‐analysis to quantify the response mechanisms of the upland CH 4 sink. Results show that warming, reduced precipitation, and elevated carbon dioxide concentrations significantly strengthened the CH 4 sink, while increased precipitation and nitrogen addition weakened it. Interactive effects were also observed: low‐level nitrogen deposition acted antagonistically with increased precipitation, but synergistically with warming. We subsequently optimized a CH 4 oxidation model to explore the global distribution patterns and future trends under different climate scenarios. The current global upland soil CH 4 sink is estimated at approximately 37 Tg year −1 and generally shows an increasing temporal trend. Spatially, the sink exhibits heterogeneity: a greater extent of desert areas in the Northern Hemisphere leads to a lower CH 4 sink per unit area compared to the Southern Hemisphere. Future spatiotemporal trends of the soil CH 4 sink will depend on the climate pathway. Under the Shared Socioeconomic Pathway (SSP) 1–2.6 scenario, the CH 4 sink declines over time, whereas under SSP5‐8.5, it follows a unimodal trajectory. Variations in the soil CH 4 sink also differ across regions. These changes are primarily associated with atmospheric CH 4 concentrations under different climate pathways, as well as alterations in soil temperature and moisture resulting from various climate change drivers. These findings underscore the importance of the upland CH 4 sink in the global CH 4 cycle and significantly advance our understanding of its response mechanisms to climate change.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

The impact of storage conditions on quality and shelf life of fresh-cut jackfruit: a metabolomics perspective - Yuting Huang; Wenli Zhang; Wanqing Sun; Wenzhu Shen; Yifan Cheng; Yining Xia; Yanjun Zhang; Qiong Lin (Food Chemistry, 2026)

Biochar promoted soil organic carbon accumulation and aggregate stability by increasing the content of organic complex metal oxides in paddy soil - Jiajun Wu; Bin Zhou; Zichuan Li; Cheng Liu; Yan Li; Yulin Wang; Ning Zhao; Zhuozhe Wang; Yanjun Chai; Antonio Scopa; Marios Drosos; Vishnu D. Rajput; et al. (Soil and Tillage Research, 2025)

Structural characterization of water-soluble pectin in NFC orange juice during cloud destabilization - Shiying Yang; Jian Xu; Siying Liu; Yujie Cheng; Fengjiao Cai; Yanjun Zhang; David Julian McClements; Peiyi Shen; Qian Li (Food Chemistry, 2025)

The Holocene stalagmite trace element and Sr isotope records from Central China and the inferred hydroclimate changes - Yuting Wu; Yanjun Cai; Fugui Xiao; Mei He; Shouyi Huang; Xiangkun Zhai; Ruoxin Li; Gang Xue; Hanying Li; Chunlei Zong; Hai Cheng (Chemical Geology, 2025)

Chrysin enhances sunitinib sensitivity in renal cell carcinoma by inducing ferroptosis via targeting PI3K/Akt/GPX4 pathway - Zixuan Chen; Weiyuan Li; Boshen Jia; Guohuan Yin; Zongrun Sun; Yanjun Tong; Sheng Cheng; Min Liu (Toxicology and Applied Pharmacology, 2025)

Facilitating carrier kinetics in dual S-Scheme heterojunctions through interface regulating strategy for H2O2 generation and nizatidine degradation - Sheng Liu; Yanjun Zhang; Jun Du; Yuan Xue; Cheng Huang; Zushun Xu; Peng Wang; Zhengrong Wei; Zhanhui Yuan; Guangfu Liao; Qing Li (Chemical Engineering Journal, 2025)

Effects of rice straw biochar application rates on soil aggregate biogeochemistry and linkages to microbial community structure and enzyme activities - Jiajun Wu; Zichuan Li; Yong Li; Jiawen Liu; Cheng Liu; Yanjun Chai; Chao Ai; Qaiser Hussain; Marios Drosos; Shengdao Shan (Soil and Tillage Research, 2025)

Metabolite-derived spectral modelling can differentiate heat and drought stress under hot-dry environments - Wanlu Zhong; K.H. Cheng; Laiyin Zhou; Jiaoping Zhang; Fan Zhang; Guoyang Feng; Xinyu Zhang; Qin Ma; Yanjun Su; Shichao Jin; Hon-Ming Lam; Jin Wu (Remote Sensing of Environment, 2025)

Comparative unravelling the antifungal activity and mechanism of oleuropein and matrine inhibiting the growth of phytopathogen Fusarium spp. - Jiaxin He; Jianmei Dong; Wenwen Zhang; Yaya Cheng; Jiali Xie; Xufeng Ji; Fazal Ullah; Yanjun Ma; Weibao Kong (Pesticide Biochemistry and Physiology, 2025)

Mechanism of action of pulsed electric field on lactoferrin: Functional properties, structure and aggregation behavior - Yuhui Ding; Hongfang Cao; Cheng Zhang; Yanjun Tong; Caiyun Wang; Jian He; Wei Zhao; Ruijin Yang (Food Chemistry, 2025)

Chemical recycling of polyvinyl chloride: Recent progress in pretreatment dechlorination and chlorine recycling - Lidong Liu; Beibei Yan; Tiecheng Liu; Yanjun Zhang; Runping Du; Jinglan Wang; Guanyi Chen; Zhanjun Cheng (Resources, Conservation and Recycling, 2025)

Annually laminated stalagmite inferred variations of precipitation and temperature in northern China over the last 150 years - Yingying Wei; Yanjun Cai; Xing Cheng; Gang Xue; Kang’en Zhou; Le Ma; Yanbin Lu; Shouyi Huang; Mei He; Hai Cheng; R. Lawrence Edwards (Climate Dynamics, 2025)

The influence of coating defects, cathodic protection and Pseudomonas aeruginosa on the corrosion behavior of EH40 steel - Xue Zhang; Yanjun Liu; Shiqiang Chen; Xin Cheng; Guangzhou Liu (International Biodeterioration & Biodegradation, 2025)

The performance of an embankment over soft clay under rainfall with tension cracks at soil-pile interface caused by lateral deformation - Xing Wei; Shitao Cheng; Yanjun Li; Rui Chen; Zijian Wang; Fan Tang; Bingkun Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Proline improves the developmental competence of in vitro matured porcine oocytes by enhancing mitochondrial function - Yazhuo Cheng; Jiyong Shang; Xilong Jia; Yongda Zhao; Jing Liu; Yanjun Huan; Jinghe Tan; Mingju Sun (Theriogenology, 2025)

Millennial-scale climate variability of the Asian summer monsoon over the last 690,000 years: insights from cave records - Xiaowen Niu; Jian Wang; Le Kang; Youwei Li; Haiwei Zhang; Xiyu Dong; Hanying Li; Lijuan Sha; Liang Yi; Ashish Sinha; Youfeng Ning; Xue Jia; et al. (Science Bulletin, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Comparative analysis of chromatin accessibility in porcine oocytes from follicles of different sizes - Yazhuo Cheng; Jingyu Li; Jiyong Shang; Xilong Jia; Yeling Bi; Jiaxu Gu; Nan Jiang; Yanjun Huan; Youwei Li; Mingju Sun (Research in Veterinary Science, 2025)

An evaluation method of hydraulic fracture propagation behavior in rock containing natural fractures based on fractal dimension - Yulong Liu; Yanjun Zhang; Yuxiang Cheng; Ziwang Yu; Xuefeng Gao; Lei Liu (Geomechanics for Energy and the Environment, 2025)

High-temperature treated oil-rich bedded rock layer and deterioration mechanism of heat transfer performance - Yanjun Shen; Ziyi Li; Cheng Peng; Jianshuai Hao (Bulletin of Engineering Geology and the Environment, 2025)

Early-Middle Holocene climate change and its impact on the succession of Neolithic cultures in southern Hangzhou Bay - Jing Lu; Haiwei Zhang; Rui Zhang; Jiahui Cui; Yanyan Bao; Xiaowen Niu; Yanjun Cai; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The catalytic mechanism for H2 production on MgO-CaO materials through the water gas shift reaction: A DFT study - Pengfei Zhao; Yanjun Wu; Chuanjiang Yang; Ke Wang; Peisheng Li; Edward J. Anthony; Cheng Fang (Gas Science and Engineering, 2025)

A novel machine learning approach for reservoir temperature prediction - Haoxin Shi; Yanjun Zhang; Yuxiang Cheng; Jixiang Guo; Jianqiao Zheng; Xin Zhang; Yude Lei; Yongjie Ma; Lin Bai (Geothermics, 2025)

Reduction characteristics and mechanism of mechanically activated iron ore powder by lignin - Wangsheng Cheng; Yanjun Wang; Rufei Wei; Jiaxin Li; Hongming Long (Fuel, 2025)

High-risk nuclide screening and parameter sensitivity analysis based on numerical simulation and machine learning - Xin Zhang; Yanjun Zhang; Yu Zhang; Yuxiang Cheng; Qiangbin Liu; Hao Deng; Yongjie Ma; Lin Bai; Lei Liu (Journal of Hazardous Materials, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Metal-ion-binding properties of glycyrrhiza polysaccharide extracted from Licorice: Structural characterization and potential application in drug delivery - Yanjun Yang; Mengli Yu; Yulin Mo; Yue Cheng; Bin Huang; Weilin Wang; Maomao Zhu; Xiaobin Jia; Liang Feng; Bing Yang (Carbohydrate Polymers, 2024)

Environmental DNA (eDNA) reveals the effects of cascade dam development on the distribution patterns of aquatic biodiversity in mountain rivers - Yanjun Shen; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Ruli Cheng (Frontiers in Marine Science, 2024)
The rich and special biodiversity in mountain rivers is experiencing a continuous decline due to the influence of climate change and anthropogenic factors. To explore the alterations in the distribution of aquatic biodiversity in mountain rivers in the context of cascade dam development, the environmental DNA (eDNA) metabarcoding technique was used to examine the aquatic biodiversity of the Wujiang River, a representative mountain river with an 11-stage cascade dam. In this study, a comprehensive analysis of aquatic organisms in the Wujiang River mainstem was conducted, and 17 phyla and 38 classes were detected in the 36 water samples. The most abundant group is the benthic organisms, and the least abundant group is the amphibians. The results of the diversity analysis showed a clear longitudinal distribution pattern of aquatic organisms along the altitudinal gradient, with higher richness of aquatic organism communities the further to the lower reaches. Meanwhile, RDA analysis revealed that altitude, dissolved oxygen, reservoir length, and reservoir construction time were the key environmental factors influencing the distribution of aquatic organisms in the Wujiang River mainstem. The findings of this research also showed the applicability of the eDNA method in detecting aquatic biodiversity.

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

Dual pathways of aragonite-to-calcite transformation in stalagmites: Implications for paleoclimate reconstructions - Rui Zhang; Haiwei Zhang; Christoph Spötl; Hai Cheng; Yanjun Cai; Carlos Pérez-Mejías; Xiyu Dong; Lijuan Sha; Youwei Li; Liangcheng Tan; Jingjie Zang; Xunlin Yang; et al. (Geochimica et Cosmochimica Acta, 2024)

A yarn-based sweat-activated battery constructed with conjugated electrospun nanofiber separators as a durable and high-capacity power source in textile electronics - Yanling Zheng; Huijun Sun; Yanjun Cheng; Wenhu Gao; Chenyu Wang; Jun Ju; Min Li; Xuemei Xiang; Wei Sun; Wei Wang; Zhisong Lu; Yan Qiao (Chemical Engineering Journal, 2024)

eDNA reveals spatial homogenization of fish diversity in a mountain river affected by a reservoir cascade - Ruli Cheng; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Yang Luo; Qiliang Chen; Zhihao Liu; Yingwen Li; Yanjun Shen (Journal of Environmental Management, 2024)

Scalable, flexible, ultra-strong, free-standing papery all carbon nanotube membrane with excellent separation and antifouling properties - Yang Yang; Yuhang Cheng; Si Ling; Yanjun Wan; Zhu Xiong; Chunhong Li; Jiangyan Lu; Li Yu; Gaosheng Zhang; Shuaifei Zhao (Chemical Engineering Journal, 2024)

Cenozoic structural and tectonic evolution in the Western Xihu Basin, East China Sea Shelf Basin - Bin Xu; Zhiping Wu; Yanjun Cheng; Johannes M. Miocic; Yining Dai; Yichen Chu (International Journal of Earth Sciences, 2024)

Regulation of interfacial polymerization by organic base for high-permselective nanofiltration - Huiying Ding; Yuting Liu; Zhong Zhang; Yanjun Cheng; Jiahao Mo; Lu Elfa Peng; Cheng Xiang; Hongchang Pei; Xianhui Li (Desalination, 2024)

An integrated study of constraining the initial 230Th of a stalagmite and its implications - Shouyi Huang; Yanjun Cai; Hai Cheng; Gang Xue; Xing Cheng; Mei He; Ruoxin Li; Le Ma; Yingying Wei; Yanbin Lu; Ling Yang; R. Lawrence Edwards (Quaternary Geochronology, 2024)

A prospect analysis of the Upper Oligocene sandstone reservoirs of the Wenchang 9 block, Pearl River Mouth Basin, northern South China Sea margin - Jie Zhang; Elena Konstantinovskaya; Zhiping Wu; Yanjun Cheng; Bin Xu (Marine and Petroleum Geology, 2024)

Solar-driven biomass chemical looping gasification using Fe3O4 for syngas and high-purity hydrogen production - Dequan Xu; Bo Wang; Xian Li; Yoke Wang Cheng; Wenming Fu; Yanjun Dai; Chi-Hwa Wang (Chemical Engineering Journal, 2024)

The Numerical Investigation of Solid–Liquid Two-Phase Flow Characteristics Inside and Outside a Newly Designed 3D Sediment Trap - Zhihao Xu; Zihang Fei; Yusen Zhu; Cheng Wang; Xiuqing Yang; Lei Guo; Gang Xue; Yanjun Liu (Journal of Marine Science and Engineering, 2023)
Sediment transport serves as a link for material exchange between land and sea. Using sediment traps, we can observe the capture and transport processes of sediments. Based on the sediment particle size distribution characteristics in Jiaozhou Bay, this paper analyzes the influence of a newly designed 3D sediment trap on the water–sand two-phase flow process inside and outside a trap device during its operation. Meanwhile, under a certain concentration condition, a numerical formula model is researched and proposed to evaluate the impact of the device’s structure, the environmental flow speed, and the particle size on particle capture efficiency. This model is based on the CFD-DPM coupling in Fluent 2021R1 software, and the particle filtration process is solved using a combination of porous media and UDF functions. Finally, by analyzing the distribution of sediment movement in the fluid domain, two concepts, namely the percentage of particles entering the tube and the effective capture rate, are proposed. Suggestions for optimizing the structure of the trap are put forward to achieve optimal capture effects.

Historical trends and pollution assessment of heavy metals in core sediments from the Jiangsu offshore area, China - Li He; Shenghui Jiang; Xuhui Chen; Haiyan Cheng; Peng Ye; Lu Chen; Yuan Liu; Yanjun Yin; Xing Leng (Regional Studies in Marine Science, 2023)

Experimental studies on the effects of thermal damage in coal-derived mudstones caused by high temperatures - Yanjun Shen; Ziyi Li; Cheng Peng; Bohan Yang; Tianchi Ma (Acta Geodaetica et Geophysica, 2023)

New insights on the breakage mechanism of magnetite quartzite via high voltage pulse discharge: liberation, property difference, micro morphology, and numerical simulation - Yonghong Qin; Yuexin Han; Peng Gao; Yanjun Li; Yanxia Guo; Fangqin Cheng (Minerals Engineering, 2023)

Adhesive injectable cellulose-based hydrogels with rapid self-healing and sustained drug release capability for promoting wound healing - Lu Li; Lixin Wang; Xinxin Luan; Yanjun Pang; Kefeng Zhang; Yushuai Cheng; Zhe Ji; Jinhui Pang (Carbohydrate Polymers, 2023)

Application of eDNA metabarcoding for monitoring the fish diversity of the Jiangjin to Fuling section of the upper reaches of the Yangtze River - Ruli Cheng; Yang Luo; Qinghua Li; Yufeng Zhang; Zhihao Liu; Qiliang Chen; Yingwen Li; Yanjun Shen (Hydrobiologia, 2023)

Numerical study on a coaxial geothermal exchanger equipped with a new inner tube: Entropy generation, thermodynamic irreversibility analysis and exergy efficiency performance evaluation - Qiangbin Liu; Yanjun Zhang; Xin Zhang; Yuxiang Cheng; Ji Luo; Jianqiao Zheng; Yulong Liu; Junqing Lou (Journal of Cleaner Production, 2023)

Removal of tar from waste textiles by molten carbonates pyrolysis in bubbling reactor - Yaohong He; Yanjun Hou; Cheng Wang; Shan Wang; Yi Wei (Fuel, 2023)

Root predominant overexpression of iaaM and CKX genes promotes root initiation and biomass production in citrus - Dan Tang; Yanjun Li; Longmei Zhai; Wei Li; Rahul Kumar; Huseyin Yer; Hui Duan; Baoping Cheng; Ziniu Deng; Yi Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Promoting initiation and biomass production of roots is significant for plant-based industries including using roots as bioreactors. Two citrus genotypes, Carrizo and US-897, were used as model plants to test the effects of root-predominantly overexpressed the iaaM (indoleacetic acid-tryptophan monooxygenase) gene and a CKX (a cytokinin oxidase/dehydrogenase) gene. The iaaM transgenic lines exhibited markedly faster root initiation, more root numbers, and higher root biomass compared to their wild-type counterparts. The transgenic iaaM + CKX plants also exhibited similar phenotypes, albeit to a lesser extent than the iaaM plants. Molecular analysis revealed an auxin-responsive CsGH3.1 gene was up-regulated in the iaaM roots and iaaM + CKX roots, and a cytokinin-responsive gene CsARR5 gene was down-regulated in the iaaM + CKX roots. Our results demonstrate that root predominant overexpression of the iaaM or both the iaaM and CKX genes drastically enhances the initiation, growth and biomass production of roots. These results provide additional support that manipulation of auxin and cytokinin levels in roots via transgenic or gene-editing technologies may benefit production of high-value secondary metabolites using roots as bioreactors and also improve rooting of recalcitrant plant species.

Heavy metal concentration profiles and pollution assessment in the Jiangsu offshore area, China - Lihui Xiang; Shenghui Jiang; Haiyang Cheng; Yanfen Wang; Qiang Liu; Yanjun Yin; Xing Leng (Marine Pollution Bulletin, 2023)

Mapping foliar photosynthetic capacity in sub-tropical and tropical forests with UAS-based imaging spectroscopy: Scaling from leaf to canopy - Shuwen Liu; Zhengbing Yan; Zhihui Wang; Shawn Serbin; Marco Visser; Yuan Zeng; Youngryel Ryu; Yanjun Su; Zhengfei Guo; Guangqin Song; Qianhan Wu; He Zhang; et al. (Remote Sensing of Environment, 2023)

Combined effect of heating and enzymatic hydrolysis on the dispersibility and structure properties of egg white powder - Tingting Wang; Cuihua Chang; Wanying Cheng; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Journal of Food Engineering, 2023)

Dynamic effects of miR-20a-5p on hippocampal ripple energy after status epilepticus in rats - Xinyu Zhang; Yanjun Yi; Li Cheng; Hengsheng Chen; Yue Hu (Experimental Brain Research, 2023)

Artificial potential incorporated adaptive fixed-time sliding mode control for target capture - Bicheng Cai; Cheng Wei; Chengfei Yue; Yanjun Yu; Xueqin Chen; Yunhai Geng (Advances in Space Research, 2023)

Basement structures exert a crucial influence on the structural configuration of later rift development: Insights from the Shanan and Chengbei sag, Bohai Bay Basin - Yanjun Cheng; Zhiping Wu; Wen Su; Mingming Chen; Jie Zhang; Yuqing Liu; Qingbo Wu (Marine and Petroleum Geology, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Structural characteristics and genetic mechanism of transfer zones in an extensional rift zone: An example from the Xihu Sag, East China Sea Basin - Yanjun Cheng; Zhiping Wu; Bin Xu; Jie Zhang; Yichen Chu; Yining Dai; Lili Xu; Wenjie Sun; Saiting Ma (Tectonophysics, 2023)

A novel reutilization of ash from biomass gasification process: Feasibility and products improvement analysis - Qianqian Guo; Beibei Yan; Yanjun Hu; Xiang Guo; Wenzhu Wu; Zhanjun Cheng; Guanyi Chen; Li'an Hou (Fuel, 2023)

Rapid determination and health risk assessment of neonicotinoids in source water and tap water of the tropical Hainan Island, China - Zengheng Xiong; Yan Wu; Yang Zhou; Shuhai He; Danyu Huang; Mingshan Zhang; Yanjun Jiang; Long Cheng; Zhendong Zhao; Hongwei Zhao; Huan Lin (Environmental Science and Pollution Research, 2023)

Associations between congenital heart disease and air pollutants at different gestational weeks: a time-series analysis - Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Zhou; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Geochemistry and Health, 2023)

Ultrafast loose nanofiltration membrane intercalated by in-situ grown nanoparticles for dye purification and reuse - Yuting Liu; Jiahao Mo; Huiying Ding; Yanjun Cheng; Zhong Zhang; Chen Wang; Xianhui Li (Desalination, 2023)

Seismicity induced by geological CO2 storage: A review - Yuxiang Cheng; Wenna Liu; Tianfu Xu; Yanjun Zhang; Xinwen Zhang; Yunyan Xing; Bo Feng; Yi Xia (Earth-Science Reviews, 2023)

A new automatic quality control system for ocean profile observations and impact on ocean warming estimate - Zhetao Tan; Lijing Cheng; Viktor Gouretski; Bin Zhang; Yanjun Wang; Fuchao Li; Zenghong Liu; Jiang Zhu (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Orbital‐ to millennial‐scale variation of the speleothem δ 18 O record during Marine Isotope Stages 5 to 3 on the southeast Chinese Loess Plateau and its climatic and environmental implications - YANJUN CAI; HAI CHENG; XING CHENG; ZHENGGUO SHI; YANBIN LU; LE MA; CARLOS PÉREZ‐MEJÍAS; HAIWEI ZHANG; YINGYING WEI; GANG XUE; HANYING LI; MEI HE; et al. (Journal of Quaternary Science, 2023)
The Chinese Loess Plateau (CLP) is located in northern China, a region climatically dominated by the East Asian monsoon. Speleothem records from this region are crucial to fully understand the variability of the East Asian summer monsoon (EASM) and reconcile the disparity seen between loess records and speleothem δ 18 O records for the EASM. Here, we present an absolutely dated stalagmite isotope record spanning most of Marine Isotope Stage (MIS) 5 to MIS 3 from Xiaotian Cave, southeast CLP. The Xiaotian speleothem δ 18 O record is dominated by precessional variations and punctuated by notable millennial‐scale oscillations; in particular, the δ 18 O values in MIS 5e, 5c and 5a were in the same range, consistent with other speleothem δ 18 O records from the EASM region within quoted errors, verifying the difference between speleothem δ 18 O and loess records (e.g. magnetic susceptibility) and the proposition that those two archives may record different aspects of the EASM changes. The similar values in MIS 5e, 5c and 5a observed from the speleothem δ 18 O records in EASM regions, incompatible with the relatively higher North Hemisphere Summer Insolation (NHSI) during MIS 5e, were probably caused by an equivalent or even increased contribution of 18 O‐enriched moisture from the South China Sea and North Pacific, implying that an El Niño‐like state existed during MIS 5e. The Xiaotian δ 18 O values increased abruptly at ~121.7 thousand years (kyr) before the present ( bp , present refers to ad 1950), consistent with the trend seen in previously reported Chinese speleothem δ 18 O records, indicating an abrupt regime shift in atmospheric circulations or hydroclimate conditions in the Asian monsoon systems. It cannot be definitely ruled out that an increase in sea ice extent in the northern North Atlantic, responding to a decrease of NHSI, reached a threshold to have led to abrupt changes in the Asian summer monsoon (ASM) through rapid shifts in the position of circulation of the westerlies and/or in the position of Intertropical Convergence Zone (ITCZ). Here, we hypothesized that sea surface cooling in the tropical Indian and Pacific Ocean caused by the decreased summer insolation reached a threshold that eventually resulted in an abrupt shift to more positive precipitation δ 18 O, either through weakened convection over the tropical ocean, or through abrupt shifts in moisture transport and cycling of tropical moisture sources for the ASM. The Xiaotian speleothem δ 18 O record also shows centennial‐scale variability with amplitude up to 3‰ within MIS 5e. These changes are similar to variations recorded by the speleothem δ 18 O record from Tianmen Cave on the south‐central Tibetan Plateau and Shangxiaofeng Cave in Shandong Province, northern China, suggesting a heightened sensitivity of precipitation δ 18 O to climate changes at the marginal zone of the ASM even during the warm and humid MIS 5e interglacial. Climatic oscillations during MIS 5e appear to be comparable to those typical of the Holocene, implying rather unstable climate conditions during the Last Interglacial.

Can the marketization of urban land transfer improve energy efficiency? - Yanjun Yang; Rui Xue; Xiaoxi Zhang; Yutai Cheng; Yuli Shan (Journal of Environmental Management, 2023)

Microwave heating instead of blanching to produce low-fat French fries - Cheng Zhang; Xiaomei Lyu; Rana Muhammad Aadil; Yanjun Tong; Wei Zhao; Ruijin Yang (Innovative Food Science & Emerging Technologies, 2023)

Pulsed electric field as a promising technology for solid foods processing: A review - Cheng Zhang; Xiaomei Lyu; Rai Naveed Arshad; Rana Muhammad Aadil; Yanjun Tong; Wei Zhao; Ruijin Yang (Food Chemistry, 2023)

The Mesozoic tectonic evolution of the East China Sea Basin: New insights from 3D seismic reflection data - Yanjun Cheng; Zhiping Wu; Bin Xu; Yining Dai; Yichen Chu; Jie Zhang; Mingming Chen; Saiting Ma; Wenjie Sun; Lili Xu (Tectonophysics, 2023)

A case study on the migration of nuclides in the coupled vadose zone-groundwater system at a proposed spent fuel reprocessing site in Gansu, China - Xin Zhang; Yanjun Zhang; Yu Zhang; Xuefeng Gao; Yuxiang Cheng; Yongjie Ma; Peng Zhang; Xuhong Wang (Journal of Hydrology, 2023)

Using one-dimensional convolutional neural networks and data augmentation to predict thermal production in geothermal fields - Yunxing Yang; Yanjun Zhang; Yuxiang Cheng; Zhihong Lei; Xuefeng Gao; Yibin Huang; Yueqiang Ma (Journal of Cleaner Production, 2023)

Mapping China’s planted forests using high resolution imagery and massive amounts of crowdsourced samples - Kai Cheng; Yanjun Su; Hongcan Guan; Shengli Tao; Yu Ren; Tianyu Hu; Keping Ma; Yanhong Tang; Qinghua Guo (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Genetic Diversity of Jinshaia sinensis (Cypriniformes, Balitoridae) Distributed Upstream of the Yangtze River - Yang Luo; Yufeng Zhang; Ruli Cheng; Qinghua Li; Yu Zhang; Yingwen Li; Yanjun Shen (Fishes, 2023)
The upper reaches of the Yangtze River (upper YR) are a biological zone with extremely rich fish diversity, especially endemic fish. However, long-term human interference, such as environmental pollution and cascade hydropower construction, has significantly changed the habitat of many fish and is threatening the number and genetic diversity of fish populations. Jinshaia sinensis is a typical small and endemic but rare fish that is found in the upper YR, and its genetic diversity and structure still need further study. To understand the current levels of genetic diversity in J. sinensis, we analyzed the genetic diversity, population history, genetic structure, etc., of three J. sinensis populations based on two mitochondrial genes (the cytochrome-c oxidase subunit I, COI, and cytochrome-b gene, Cytb) and two nuclear genes (recombination-activating protein 1, RAG1, and rhodopsin, RH). The genetic diversity analysis indicated that J. sinensis had high genetic diversity, with high haplotype diversity (h) and nucleotide diversity (Pi). Population pairwise FST analysis revealed a significant genetic divergence between the Lijiang and Luzhou populations for all genes and between the Panzhihua and Luzhou populations, except for the COI gene; however, analyses of molecular variance (AMOVA) showed no significant geographic genetic structure among populations, and gene flow analysis also indicated a certain degree of gene exchange among populations. Haplotype network structure analyses revealed low levels of shared haplotypes among populations. Neutrality test and mismatch distribution results indicated that only the Lijiang population had experienced obvious population expansion. Overall, these results indicate that J. sinensis is still a single evolutionarily significant unit, but when considering the threat of habitat disturbance to the population, it is still necessary to carry out long-term genetic monitoring on J. sinensis and on other endemic fishes with similar ecological habits in order to maintain the genetic diversity of fishes in the upper YR.

Development and application of a 6000-meter double decelerating lander - Lei Guo; Xiuqing Yang; Gang Xue; Cheng Wang; Zihang Fei; Shaotong Zhang; Yanjun Liu; Kai Lu; Yuan Yang (Frontiers in Marine Science, 2023)
The deep-sea lander is an important equipment for in-situ detection and monitoring. It is of great significance to understand the benthic boundary layer’s physical, chemical, and ecological environment. A 6000-meter double decelerating lander was created to meet the deployment requirements of underwater detection and monitoring, allowing for long-term in-situ monitoring of several benthic boundary layer components. Protection of the installed ocean bottom seismometer (OBS) is required due to the lander’s and OBS’s different impact resistances. The double decelerating unit enables the OBS to avoid colliding with the seabed when the lander lands and then collides with the seabed at a slow speed rather than the speed at which the lander falls, which is intended to safeguard OBS from damage. To ensure a safe deployment, the lander’s static analysis and simulation were performed using ANSYS, and the motion characteristics of the application process were derived. Numerous data have been obtained after the lander’s successful application in the South China Sea. The lander provides an investigation approach for marine science and geochemistry, complementing a technical approach to marine environmental investigations.

PM2.5-related DNA methylation and the association with lung function in non-smokers - Ge Mu; Xiuquan Nie; Shijie Yang; Zi Ye; Man Cheng; Lieyang Fan; Weihong Qiu; Qiyou Tan; Min Zhou; Yanjun Guo; Weihong Chen (Environmental Pollution, 2023)

Association between air pollutants and neural tube defects during pregnancy in Lanzhou, China: a time series analysis - Yan Yang; Li Zhou; Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Pan; Yanbei Huo; Ruijuan Wang; Yupei Ba; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2023)

Cenozoic rifting and inversion of Beibuwan Basin and its linkage with the strike-slip movement along the Ailao Shan-Red River Shear Zone - Yanjun Cheng; Zhiping Wu; Jie Zhang; Yuqing Liu; Zhengkai Wang; Yining Dai (International Geology Review, 2022)

Time series analysis on association between ambient air pollutants and orofacial clefts during pregnancy in Lanzhou, China - Yanyan Liu; Li Zhou; Wenling Zhang; Yanjun Yang; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2022)

Late Mesozoic rifting and its deep dynamic mechanisms in the central Sulu orogenic belt: Records from Lingshan Island - Tengfei Zhou; Yaoqi Zhou; Nina Søager; Paul Martin Holm; Zhenkai Zhang; Jun Wang; Zhao Liang; Hongyu Mu; Yanjun Cheng; Feifei Liu; Miao Wang; Yue Zhang; et al. (Science China Earth Sciences, 2022)

Urinary polycyclic aromatic hydrocarbon metabolites and depression: a cross-sectional study of the National Health and Nutrition Examination Survey 2005–2016 - Xiaobing Feng; Ruyi Liang; Da Shi; Dongming Wang; Yanjun Guo; Weihong Qiu; Man Cheng; Tao Xu; Chaoqian Dong; Min Zhou; Weihong Chen (Environmental Science and Pollution Research, 2022)

Late Jurassic to early Cretaceous magnetostratigraphy of scientific drilling core LK-1 in the Lingshan Island of Riqingwei Basin, eastern China - Yanjun Cheng; Zhiping Wu; Xiaoyu Liu; Yaoqi Zhou; Yining Dai; Tongjie Zhang; Tengfei Zhou (Science China Earth Sciences, 2022)

Preparation of high-precision CO 2 with known triple oxygen isotope for oxygen isotope analysis - Lijuan Sha; Sasadhar Mahata; Pengzhen Duan; Baoyun Zong; Youfeng Ning; Pu Zhang; Jian Wang; Yanjun Cai; Hai Cheng (Isotopes in Environmental and Health Studies, 2021)

Investigation on Reservoir Stimulation Characteristics in Hot Dry Rock Geothermal Formations of China During Hydraulic Fracturing - Yuxiang Cheng; Yanjun Zhang; Ziwang Yu; Zhongjun Hu (Rock Mechanics and Rock Engineering, 2021)

Orbital-scale Asian summer monsoon variations: Paradox and exploration - Hai Cheng; Haiwei Zhang; Yanjun Cai; Zhengguo Shi; Liang Yi; Chenglong Deng; Qingzhen Hao; Youbing Peng; Ashish Sinha; Hanying Li; Jingyao Zhao; Ye Tian; et al. (Science China Earth Sciences, 2021)

Effectiveness of predicting spatial contaminant distributions at industrial sites using partitioned interpolation method - Pengwei Qiao; Sucai Yang; Wenxia Wei; Peizhong Li; Yanjun Cheng; Shuang Liang; Mei Lei; Tongbin Chen (Environmental Geochemistry and Health, 2021)

A multiple-proxy stalagmite record reveals historical deforestation in central Shandong, northern China - Liangcheng Tan; Wen Liu; Tianli Wang; Peng Cheng; Jingjie Zang; Xiqian Wang; Le Ma; Dong Li; Jianghu Lan; R. Lawrence Edwards; Hai Cheng; Hai Xu; et al. (Science China Earth Sciences, 2020)

Population, urbanization and economic scenarios over the Belt and Road region under the Shared Socioeconomic Pathways - Cheng Jing; Hui Tao; Tong Jiang; Yanjun Wang; Jianqing Zhai; Lige Cao; Buda Su (Journal of Geographical Sciences, 2020)

Comparison of common spatial interpolation methods for analyzing pollutant spatial distributions at contaminated sites - Pengwei Qiao; Peizhong Li; Yanjun Cheng; Wenxia Wei; Sucai Yang; Mei Lei; Tongbin Chen (Environmental Geochemistry and Health, 2019)

Is Chinese stalagmite δ18O solely controlled by the Indian summer monsoon? - Dong Li; Liangcheng Tan; Yanjun Cai; Xiuyang Jiang; Le Ma; Hai Cheng; R. Lawrence Edwards; Haiwei Zhang; Yongli Gao; Zhisheng An (Climate Dynamics, 2019)

Application of Avaatech X-ray fluorescence core-scanning in Sr/Ca analysis of speleothems - Dong Li; Liangcheng Tan; Fei Guo; Yanjun Cai; Youbin Sun; Gang Xue; Xing Cheng; Hong Yan; Hai Cheng; R. Lawrence Edwards; Yongli Gao; Jessica Kelley (Science China Earth Sciences, 2019)

Flotation and adsorption of quartz with the new collector butane-3-heptyloxy-1,2-diamine - Zhouyueyang Cheng; Yimin Zhu; Yanjun Li; Yuexin Han (Mineralogy and Petrology, 2019)

Clinical evaluation of a panel of multiplex quantitative real-time reverse transcription polymerase chain reaction assays for the detection of 16 respiratory viruses associated with community-acquired pneumonia - Dan Zhang; Haiyan Mao; Xiuyu Lou; Junhang Pan; Hao Yan; Hongfeng Tang; Yan Shu; Yun Zhao; Xiaoli Cheng; Hong Tao; Yanjun Zhang; Xuejun Ma (Archives of Virology, 2018)

Transcriptome analysis of alternative splicing in different moso bamboo tissues - Long Li; Qianqian Shi; Dan Hou; Zhanchao Cheng; Juan Li; Yanjun Ma; Xueping Li; Shaohua Mu; Jian Gao (Acta Physiologiae Plantarum, 2018)

Decreasing monsoon precipitation in southwest China during the last 240 years associated with the warming of tropical ocean - Liangcheng Tan; Yanjun Cai; Zhisheng An; Hai Cheng; Chuan-Chou Shen; Yongli Gao; R. Lawrence Edwards (Climate Dynamics, 2017)

Occurrence and Partitioning of Antibiotics in the Water Column and Bottom Sediments from the Intertidal Zone in the Bohai Bay, China - Dengmiao Cheng; Yujia Xie; Yanjun Yu; Xinhui Liu; Shengnan Zhao; Baoshan Cui; Junhong Bai (Wetlands, 2016)

Risk factors of severe hand, foot and mouth disease complicated with cardiopulmonary collapse - Chunlan Song; Cheng Yibing; Yanjun Guo; Zhipeng Jin; Yajie Cui; Xue Gu (Infectious Diseases, 2015)

Analysis of molecular variation of porcine reproductive and respiratory syndrome virus in Central China from 2006 to 2012 - Yuejun Shi; Zhibin Hu; Zhenghui Xiong; Yanjun Zhou; Xin Jin; Changqin Gu; Xueying Hu; Guofu Cheng; Nianhua Song; Wanpo Zhang (Archives of Virology, 2013)

LC determination and pharmacokinetic study of the main phenolic components of Portulaca oleracea L. extract in rat plasma after oral administration - Zhongzhe Cheng; Dong Wang; Wenjie Zhang; Yang Du; Yunjiao Wang; Yanjun Zhai; Xixiang Ying; Tingguo Kang (Natural Product Research, 2012)

Genome-wide analysis of Aux/IAA gene family in Solanaceae species using tomato as a model - Jian Wu; Zhen Peng; Songyu Liu; Yanjun He; Lin Cheng; Fuling Kong; Jie Wang; Gang Lu (Molecular Genetics and Genomics, 2012)

Antitumor and antimetastatic activities of vesicular stomatitis virus matrix protein in a murine model of breast cancer - Wei Shi; Qingqing Tang; Xiancheng Chen; Ping Cheng; Peidu Jiang; Xiaomei Jing; Xiang Chen; Ping Chen; Yongsheng Wang; Yuquan Wei; Yanjun Wen (Journal of Molecular Medicine, 2009)

Characterization of Anthocyanidin Synthase (ANS) Gene and anthocyanidin in rare medicinal plant-Saussurea medusa - Liqin Cheng; Yanjun Xu; Erich Grotewold; Zhiping Jin; Fengyan Wu; Chunxiang Fu; Dexiu Zhao (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Genome-wide analysis of cyclin family in rice (Oryza Sativa L.) - Honggui La; Jun Li; Zhendong Ji; Yanjun Cheng; Xiuli Li; Shuye Jiang; Prasanna Nori Venkatesh; Srinivasan Ramachandran (Molecular Genetics and Genomics, 2006)

Molecular Genetic Analysis of QTLs for Ferulic Acid Content in Dried Straw of Rice (Oryza sativa L.) - Yanjun Dong; E. Tsuzuki; H. Kamiunten; Dongzhi Lin; H. Terao; M. Matsuo; Shihua Cheng (Biochemical Genetics, 2005)

Study of 1998 heavy rainfall over the Yangtze River Basin using TRMM data - Cheng Minghu; He Huizhong; Mao Dongyan; Qi Yanjun; Cui Zhehu; Zhou Fengxian (Advances in Atmospheric Sciences, 2001)